Geoprocessamento aplicado na espacialização das áreas de preservação permanente e áreas de conflitos na sub-bacia Ribeirão Hortelã - Campos, Sergio [UNESP]; Granato, Marina [UNESP]; Soares, Muriel Ciccati Emanoele [UNESP]; Cavasini, Raquel [UNESP]; Araújo, Débora Marques [UNESP]; Mashiki, Mônica Yuri [UNESP]; Ruggiero, Júnia [UNESP]; Piza, Mariana Wagner de Toledo [UNESP] (My University, 2010)
The present work aimed to analyze the conflicts of soil use in permanent preservation areas (PPA) of Stream Hortelã sub-basin - Botucatu (SP) through the use of Geographical Information Systems - SIG Idrisi Andes 15.0 and of satellite image. The area with 1405.15ha, locates among the geographical coordinates: 48o 34’ to 48o 31’ of longitudes WGr. and 22o 55’ to 22o 51’ S of latitudes S. The map of soil use of 2006 was obtained starting from the classification supervised in digital satellite image of 23/10/2006. In the digital identification of the objectives the interpretation keys were used for images and the areas were certain through GIS - IDRISI Andes 15.0. The use conflicts in the permanent preservation areas were analyzed along the drainage net and of the nascents through SIG Idrisi Andes 15.0, according to items of the goods 2 o and 3o of the Resolution no 303 of CONAMA. The permanent preservation areas (APP) discriminated along the drainage net was of 1276.04ha. However, 272.89ha of the area of PPA are busy with clean field (150.59ha), culture (109.82ha), dirty field (5.63ha) and reforestation (6.85ha) in an inadequate way (Conflict). Therefore, 98.86% of area of APP has been used inadequately.

O presente trabalho visou analisar os conflitos de uso do solo em áreas de preservação permanentes (APPs) da sub-bacia do Ribeirão Hortelã - Botucatu (SP) através do uso de Sistemas de Informações Geográficas – SIG Idrisi Andes 15.0 e de imagem de satélite. A área com 1405,15ha, situa-se entre as coordenadas geográficas: 48º 34´ a 48º 31’ de longitudes WGr. e 22º 55’ S a 22º 51’S de latitudes S. O mapa de uso do solo de 2006 foi obtido a partir da classificação supervisionada em imagem de satélite digital de 23/10/2006. Na identificação digital dos alvos foram utilizadas as chaves de interpretação para imagens e as áreas foram determinadas através do SIG – IDRISI Andes 15.0. Os conflitos de uso nas áreas de preservação permanente foram analisados ao longo da rede de drenagem e das nascentes através do SIG Idrisi Andes 15.0, conforme itens dos artigos 2º e 3º da Resolução nº 303 do CONAMA. As áreas de preservação permanente (APP) discriminadas ao longo da rede de drenagem foram de 1276,04ha. No entanto, 272,89ha da área de APP está ocupada com campo limpo (150,59ha), cultura (109,82ha), campo sujo (5,63ha) e reflorestamento (6,85ha) de forma inadequada (conflito). Portanto, 98,86% de área de APP vem sendo utilizada inadequadamente.
Keywords: PPA; Remote sensing; GIS; APPs; Sensoriamento remoto; SIG